простейшее иррациональное уравнение
одз:
x ≥ 5
возведём обе части уравнения в квадрат, получим
(√(x - = (x-5)^2
x - 3 = x^2 - 10x + 25
- x^2 + x - 3 + 10x - 25 = 0
- x^2 + 11x - 28 = 0 // : (-1)
x^2 - 11x + 28 = 0
( x - 7) ( x - 4) = 0
x = 7
x = 4 не удовлетворяет одз
ответ:
простейшее иррациональное уравнение
одз:
x ≥ 5
возведём обе части уравнения в квадрат, получим
(√(x - = (x-5)^2
x - 3 = x^2 - 10x + 25
- x^2 + x - 3 + 10x - 25 = 0
- x^2 + 11x - 28 = 0 // : (-1)
x^2 - 11x + 28 = 0
( x - 7) ( x - 4) = 0
x = 7
x = 4 не удовлетворяет одз
ответ:
x = 7